Evaluasi Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan pada Siswa SMA Menggunakan Model Countenance - Robby Kurniawan; M. E Winarno; Wasis Djoko Dwiyogo (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to determine the process of implementing physical education learning at the high school level in Banyuwangi Regency by using descriptive analytical methods in the form of formulating objectives, collecting data, comparing data (research results) with standards, making decisions and providing recommendations that refer to countenance evaluation models. The results of the assessment indicate that there are considerations at each stage of physical education learning which are shown not to be in the